1999
DOI: 10.1152/ajpheart.1999.277.1.h100
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of microtubule polymerization modulates arteriolar vasomotor tone

Abstract: Microtubules are important cytoskeletal elements that have been shown to play a major role in many cellular processes because of their mechanical properties and/or their participation in various cell signaling pathways. We tested the hypothesis that depolymerization of microtubules would alter vascular smooth muscle (VSM) tone and hence contractile function. In our studies, isolated cremaster arterioles exhibited significant vasoconstriction that developed over a 20- to 40-min period when they were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
49
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 12 publications
11
49
2
Order By: Relevance
“…4B) or 24 h (Fig. 4C) redistributed tubulin to the insoluble and soluble fractions, respectively, which is consistent with previously published observations (23). Despite the lack of effect TGF-␤ on microtubule dynamics, stabilization of microtubules by paclitaxel resulted in inhibition of TGF-␤1-induced expression of myofibroblast-associated genes, including ␣-SMA, CTGF, and SRF, both at mRNA and protein levels (Fig.…”
Section: Stabilization Of Microtubules Attenuates Tgf-␤-induced Myofisupporting
confidence: 91%
See 1 more Smart Citation
“…4B) or 24 h (Fig. 4C) redistributed tubulin to the insoluble and soluble fractions, respectively, which is consistent with previously published observations (23). Despite the lack of effect TGF-␤ on microtubule dynamics, stabilization of microtubules by paclitaxel resulted in inhibition of TGF-␤1-induced expression of myofibroblast-associated genes, including ␣-SMA, CTGF, and SRF, both at mRNA and protein levels (Fig.…”
Section: Stabilization Of Microtubules Attenuates Tgf-␤-induced Myofisupporting
confidence: 91%
“…Microtubule Disruption Promotes Myofibroblast Differentiation in a Rho/SRF-dependent, Smad-independent Manner-To examine whether microtubule polymerization state could influence fibroblast morphology and differentiation, we first utilized the direct pharmacologic inhibitor of microtubule polymerization, colchicine, which has been shown to fully depolymerize microtubules after 60 min (23). Treatment of human lung fibroblasts (HLF) with colchicine for 24 h resulted in a significant decrease in microtubule staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in our laboratories (37) showed modulation of arteriolar contractile responses to NE by the polymerization state of the microtubular network. Therefore, to examine the possible involvement of the microtubular network in the differ-ences in contractile responses to acute and prolonged NE exposure, experiments were performed in the absence and presence of the depolymerizing agent demecolcine (10 M).…”
Section: Experimental Protocolsmentioning
confidence: 68%
“…The prolonged response (4 h) to NE was then determined in the continued presence of demecolcine. Conditions for these experiments were established in previous studies (37,38).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…PHYSIOLOGY (162), whereas for microtubules it has been shown that tubular disruption induces vasoconstriction and augments vascular responsiveness to adrenergic stimulation via calcium sensitization processes dependent on the Rho kinase pathway (41, 130,131). However, the overall roles of intermediate filaments or the microtubules on the regulation of contractile function in vascular smooth muscle cells leading to control of vascular diameter is poorly understood and requires further investigation.…”
mentioning
confidence: 99%